LINGUOCULTURAL FEATURES OF PHRASEOLOGY IN UZBEK AND GERMAN LANGUAGES (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article briefly discusses phraseology in Uzbek and German. The views of the German linguist II Chernishyova on phraseology are theoretically illuminated.